Teachers’ Experiences in Integrating Digital Technology into Islamic Religious Education at SMA Harapan Mekar Medan - Handayani, Widya (Aksara Shofa, 2025)
This study aims to describe teachers' experiences in integrating digital technology into Islamic Religious Education (IRE) learning at Harapan Mekar Private High School in Medan. Conducted from July to August 2025, this study used a descriptive qualitative method with data collection techniques through direct observation in the classroom and a review of relevant literature, which were then analyzed through reduction, presentation, and conclusion drawing. The results of the study show that teachers play a role in directing the use of digital technology so that it remains in line with the objectives of religious education. However, teachers face a number of obstacles, such as limited digital skills, lack of infrastructure, resistance to change, and high administrative burdens. To overcome these obstacles, teachers implement adaptive strategies by utilizing online platforms (Google Classroom, Google Meet), mobile applications (Muslim Pro, Quran.com, Quizizz), interactive media, and social media (YouTube, Instagram) to increase student motivation and understanding. The success of technology integration is supported by school support, the role of parents, and government policies related to digital literacy, while the main obstacles remain limited resources, low digital literacy among some teachers and students, and the potential for distraction from technology. The conclusion is that the integration of digital technology in PAI learning has a positive impact in the form of increased learning effectiveness, expansion of learning resources, and strengthening of students' digital literacy. However, the success of this integration still requires a balance between the use of technology and character building through the role of teachers.